Early English Organ Music from the Middle Ages to 1837 - Routh, Francis (London Barrie & Jenkins, 1973)
This books traces the musical development of early English organ music from 1400 up to 1837. Contains five major musical periods, 305 pages, select bibliographies and an Index.
Keywords: Past; Organ; Organology; Music history; United Kingdom